PENGEMBANGAN E-LKPD INTERAKTIF LIVEWORKSHEETS PADA SISWA KELAS VIII SMPN 1 MERANGIN - Ayasa Nur Romadhani; Muhammad Jainuri; Sugeng Riyadi (Hiradika | Hira Institute, 2024)
Limited teaching materials are one thing that influences learning outcomes. Teaching materials are tools that contain systematic and programmed material. In this research, interactive E-LKPD teaching materials, live worksheets, were developed. The research objective is to develop interactive E-LKPD live worksheets that are valid, practical and effective. Type of R&D research using the ADDIE development model. The STAD type cooperative learning model was used in this research. The interactive E-LKPD was validated by 5 validators consisting of material, language, media and practitioner experts. The practicality of E-LKPD can be seen from the analysis of the practicality questionnaire and the results of student and teacher interviews. Meanwhile, the effectiveness of E-LKPD is seen from learning activities and student learning outcomes when studying using E-LKPD. The validation results obtained by material experts obtained an average of 4.57 which was categorized as very valid, the validation results obtained by language experts obtained an average of 5.00 which was categorized as very valid, the validation results obtained by media experts obtained an average of 4.20 which was categorized as very valid, and the validation results obtained by practitioners obtained an average of 4.62 categorized as very valid. The overall validation results of the live worksheet interactive E-LKPD obtained an average of 4.62 which was categorized as very valid. For the practicality of E LKPD, the percentage of 85.2% is categorized as practical. The effectiveness of a product with classical completeness of 83.33% is categorized as effective. Meanwhile, the student activity percentage of 89.41% is categorized as very active. Based on R&D research, it shows that the interactive E-LKPD live worksheets developed are valid, practical and effective. The research results become a reference for educators to develop interactive E-LKPD liveworksheets learning media on other materials.